Iván de Sorapán de Rieros, médico, humanista y divulgador - Teixidó Gómez, Francisco (2000)
In his only work Spanish Medicine in popular proverbs in our language the Extremenian Iván de Sorapán tries to explain the scientific reason of proverbs making use of personalities in the history of science and culture. I am convinced that this work has not been appreciated as it should and Sorapán does not intend to contribute to knowledge of his Age. I consider him to be just a spreader. Sorapán uses proverbs as foundation and as a starting point to explain medical issues as well as biological, gastronomic and dietetic, historical, geographical, astrono-mical and astrological, philosophical and so on.